Chemistry and chemical biology tools contributing to the discovery and functional characterization of strigolactones - Zhou, Qian; Niu, Changbin; Feng, Liang; Dong, Meixiu; Li, Xiaoxu; Kong, Bo; Li, Changsheng (Frontiers in Plant Science, 2025)
Strigolactones are a newly identified group of phytohormones that regulate plant growth and development and also act as communication signals in the rhizosphere. Beyond their well-known activity in stimulating parasitic weed germination, strigolactones function in regulating plant architecture, promoting symbiosis with arbuscular mycorrhizal fungi, and modulating responses to various environmental stresses. However, their low abundance, structural diversity, and instability have hindered comprehensive research and their practices. In this review, from the perspective of biological researcher, we summarize the powerful tools and strategies related to chemistry and chemical biology used in strigolactone area, covering analytical chemistry tools for isolation and structural elucidation, synthetic chemistry for structural elucidation and agricultural applications, chemical biology and biosynthetic strategies for functional characterization. Biosensors and probes used in monitoring strigolactone activity and signaling were also highlighted. Finally, we address current challenges and discuss future research perspectives, aiming to provoke more investigations on strigolactone biology and further boost their agricultural practices.